Performances of Free-Space Optical Communication System Over Strong Turbulence - Darusalam, Ucuk; Priambodo, Purnomo Sidi; Sudibyo, Harry; Rahardjo, Eko Tjipto (Makara Journal of Technology, 2014)
We report an experimental of free-space optical communication (FSOC) system that use tube propagation simulator (TPS) as the turbulence medium. The FSOC system use wavelength of 1550 nm at the rate transmission of 1000 Mbps and amplified with EDFA at the output of +23 dBm. Index structure of 10-15–10-13 as the representation of atmosphere index turbulences are used for simulation of intensity distribution model or scintillation. The simulation use gammagamma and K model as well. The beam wave propagation models used in simulation are plane wave, spherical wave and Gaussian wave. Spherical wave achieves highest performance via gamma-gamma in strong turbulence. While Gaussian wave achieves highest performance also via K model. We also found, characteristical FSOC system performance is calculated more accurately with gamma-gamma method for strong turbulence than K model. The performances from gamma-gamma for strong turbulence are at 22.55 dB, at 5.33´10-4, and at 9.41 ´10-6.